The eighth detective : a novel - Pavesi, Alex (New York : Henry Holt and Company, 2020)
"There are rules for murder mysteries. There must be a victim. A suspect. A detective. The rest is just shuffling the sequence. Expanding the permutations. Grant McAllister, a professor of mathematics, once sat down and worked them all out - calculating the different orders and possibilities of a mystery into seven perfect detective stories he quietly published. But that was thirty years ago. Now Grant lives in seclusion on a remote Mediterranean island, counting the rest of his days. Until Julia Hart, a sharp, ambitious editor knocks on his door. Julia wishes to republish his book, and together they must revisit those old stories: an author hiding from his past, and an editor, keen to understand it. But there are things in the stories that don't add up. Inconsistencies left by Grant that a sharp-eyed editor begins to suspect are more than mistakes. They may be clues, and Julia finds herself with a mystery of her own to solve. THE EIGHTH DETECTIVE is a cerebral, inventive novel with a modern twist, where nothing is what it seems, and proof that the best mysteries break all the rules"--
Keywords: Suspense fiction